2021
DOI: 10.1007/s10668-021-01324-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between carbon emissions and environmental sustainability during COVID-19: a new evidence from asymmetric ARDL cointegration approach

Abstract: The study aims to examine the CO 2 emissions by considering the implication of COVID-19 under strict lockdown in India. The nonlinear (asymmetric) relationship is investigated between CO 2 emission and COVID-19 with its specific determinants. The positive and negative asymmetries of COVID-19 determinants are also captured by using econometric techniques. The daily data series of CO 2 emission, new confirmed cases, confirmed deaths, and lockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…The results are also in contrast with the results of Wu et al ( 2020 ). The earlier studies confirmed the negativity of the environmental pollutants leading to COVID-19 deaths, i.e., Sarfraz et al ( 2021 ), Cicala et al ( 2021 ), and Magazzino et al ( 2020 ). The stated studies argued that ecological factors, including environmental pollutants, provide a channel to exacerbate coronavirus cases, requiring stringent environmental regulations and sound healthcare policies to improve community health Table 7 .…”
Section: Resultsmentioning
confidence: 54%
“…The results are also in contrast with the results of Wu et al ( 2020 ). The earlier studies confirmed the negativity of the environmental pollutants leading to COVID-19 deaths, i.e., Sarfraz et al ( 2021 ), Cicala et al ( 2021 ), and Magazzino et al ( 2020 ). The stated studies argued that ecological factors, including environmental pollutants, provide a channel to exacerbate coronavirus cases, requiring stringent environmental regulations and sound healthcare policies to improve community health Table 7 .…”
Section: Resultsmentioning
confidence: 54%
“…Table 3 contains the result of the bound test, which is generally used to check the binding of variables for long-term and shortterm interactions. This test is based on the mixture of integrated results of ADF to avoid spurious results (Naseem et al, 2021;Sarfraz et al, 2021). The value of F-statistics is higher than tabulated, which confirms the significance of all variables at 1% significance level.…”
Section: Methodsmentioning
confidence: 62%
“…The short-run ARDL model is employed, and the results are presented in Table 4. Before explaining the results, it is necessary to mention that the software automatically selected the lags and behavior of variables and delivered the final form (Sarfraz et al, 2020;Naseem et al, 2021;Sarfraz et al, 2021), which is presented in Table 4 under consideration of a specific set of variables. The first and third interacted variables toward the independent variable are NO 2 and SO 2 , which authorize the significance of confirmed cases and deaths of COVID-19 at a 1% level of significance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cointegration is closely related to the problem of determining a long-term relationship or longterm balance. If the time-series data are cointegrated, there is a long-term relationship between the time series data (Arnold & Glushko, 2021;Chisti, Shakeel, & Ganai, 2020;Engle & Granger, 1987;Maysami, Howe, & Rahmat, 2005;Roy, Ratya, Nuhfil, & Wahib, 2018;Sarfraz, Mohsin, Naseem, & Kumar, 2021), cointegration is a long-term relationship between variables which, although individually not stationary, but linear conditions between these variables can be stationary. Cointegration occurs when the independent and dependent variables are both a trend (time series), so they are not stationary.…”
Section: Cointegrationmentioning
confidence: 99%